GA-OH enhances the cytotoxicity of photon and proton radiation in HPV+ HNSCC cells - Chitsike, Lennox; Bertucci, Antonella; Vazquez, Marcelo; Lee, Steve; Unternaehrer, Juli J.; Duerksen-Hughes, Penelope J. (Frontiers in Oncology, 2023)
Treatment-related toxicity following either chemo- or radiotherapy can create significant clinical challenges for HNSCC cancer patients, particularly those with HPV-associated oropharyngeal squamous cell carcinoma. Identifying and characterizing targeted therapy agents that enhance the efficacy of radiation is a reasonable approach for developing de-escalated radiation regimens that result in less radiation-induced sequelae. We evaluated the ability of our recently discovered, novel HPV E6 inhibitor (GA-OH) to radio-sensitize HPV+ and HPV- HNSCC cell lines to photon and proton radiation. Radiosensitivity was assessed using various assays such as colony formation assay, DNA damage markers, cell cycle and apoptosis. Calculations for radiosensitivity indices and relative biological effectiveness (RBE) were based on the linear quadratic model. Our results showed that radiation derived from both X-ray photons and protons is effective in inhibiting colony formation in HNSCC cells, and that GA-OH potentiated radiosensitivity of the cells. This effect was stronger in HPV+ cells as compared to their HPV- counterparts. We also found that GA-OH was more effective than cetuximab but less effective than cisplatin (CDDP) in enhancing radiosensitivity of HSNCC cells. Further tests indicated that the effects of GA-OH on the response to radiation may be mediated through cell cycle arrest, particularly in HPV+ cell lines. Importantly, the results also showed that GA-OH increases the apoptotic induction of radiation as measured by several apoptotic markers, even though radiation alone had little effect on apoptosis. The enhanced combinatorial cytotoxicity found in this study indicates the strong potential of E6 inhibition as a strategy to sensitize cells to radiation. Future research is warranted to further characterize the interaction of GA-OH derivatives and other E6-specific inhibitors with radiation, as well as its potential to improve the safety and effectiveness of radiation treatment for patients with oropharyngeal cancer.